Airway management in patients with deep neck infections: A retrospective analysis. Issue 27 (July 2016) - Cho, Soo Young; Woo, Jae Hee; Kim, Yoon Jin; Chun, Eun Hee; Han, Jong In; Kim, Dong Yeon; Baik, Hee Jung; Chung, Rack Kyung
Abstract : Abstract: Securing the airway in patients undergoing surgical intervention to control a deep neck infection (DNI) is challenging for anesthesiologists due to the distorted airway anatomy, limited mouth opening, tissue edema, and immobility. It is critical to assess the risk of a potential difficult airway and prepare the most appropriate airway management method. We reviewed our anesthetic experiences managing patients with DNIs, focusing on the need for video-laryngoscope or awake fiberoptic intubation beyond a standard intubation from the anesthesiologist's perspective. When patients had infections in the masticatory space, mouth of floor, oropharyngeal mucosal space, or laryngopharynx, their airways tended to be managed using methods requiring more effort by the anesthesiologists, and more extensive equipment preparation, compared with use of a standard laryngoscope. The degree to which the main lesion influenced the airway anatomy, especially at the level of epiglottis and aryepiglottic fold was related to the airway management method selected. When managing the airways of patients undergoing surgery for DNIs under general anesthesia, anesthesiologists should use imaging with computed tomography to evaluate the preoperative airway status and a comprehensive understanding of radiological findings, comorbidities, and patients' symptoms is needed.